54‐2: Invited Paper: Holographic Display and its Applications. Issue 1 (May 2017) - Lee, Hong-Seok; An, Jungkwuen; Seo, Wontaek; Choi, Chil-Sung; Kim, Yun-Tae; Sung, Geeyoung; Seo, Juwon; Song, Hoon; Kim, Sunil; Kim, Hojung; Kim, Yongkyu; Kim, Young; et al.
Abstract : Holographic display is considered as the ultimate 3D technology. However, technical challenges in device capability and computation inhibit its commercialization. This talk addresses several approaches to overcome these challenges.